Total synthesis and biological evaluation of cell adhesion inhibitors peribysin A and B: structural revision of peribysin B - Kalmode, Hanuman P.; Handore, Kishor L.; Rajput, Raveena; Shaikh, Samir R.; Gonnade, Rajesh G.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (Organic letters, 2018)
Total synthesis of potent cell-adhesion inhibitors peribysins A and B has been accomplished for the first time in racemic form. A Diels-Alder/aldol sequence to build the skeleton and decoration of the desired functionalities of the targeted natural products using highly stereoselective operations are the highlights. The structures of synthesized peribysins were fully characterized using spectral data and single-crystal X-ray analysis. Through this total synthesis, the initially proposed structure of peribysin B has been revised. Furthermore, the cell-adhesion inhibition potential of the scaffold (two peribysins + three analogues) was confirmed using anti-adhesion assay.

Postmodification of voxelotor (GBT 440) via [Rh]-catalyzed cross dehydrogenative coupling with olefins br - Kalshetti, Rupali G.; Rajput, Raveena; Motiwala, Zenia; Reddy, D. Srinivasa; Kulkarni, Kiran A.; V. Ramana, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2022)
The directed Rh(III)-catalyzed cross dehydrogenative coupling of the pyrazole unit of the GBT-440 scaffold has been explored with simple as well as conjugated olefins to synthesize post-functionalized GBT-440 analogues. The screening of these synthesized compounds for improving the oxygen binding efficiency of the hemoglobin isolated from the sickled red blood cells revealed that some of these compounds are as good as GBT-440.
Keywords: CDC Coupling; GBT-440 (Voxelotor); Rh(III) catalysis; sickle cell anemia

Cocrystallization of multi-kinase inhibitor pazopanib with fenamic acids: improving dissolution and inhibiting cell migration - Rai, Sunil K.; Gunnam, Anilkumar; Roy, Debopriya; Rajput, Raveena; Kulkarni, Kiran; Nangia, Ashwini K. (CrystEngComm, 2023)
A multi-kinase inhibitor, pazopanib (PAZ) is cocrystallized with cyclooxygenase (COX) inhibitor fenamic acids to investigate the dissolution rate and inhibition of cell migration in VEGF-triggered HUVEC cells to test the efficacy of stoichiometric drug-drug combinations. Crystallization experiments at the sub-milligram level in an acetonitrile-methanol mixture yielded two drug-drug salt forms of PAZ with flufenamic acid (FFA) and niflumic acid (NFA) as PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named as form I) and PAZ+center dot NFA-. Structures of the crystal forms were characterized by single crystal X-ray diffraction (SC-XRD) method. Crystal structures revealed that the presence of a 2-aminopyrimidine group in PAZ is a strong partner for the carboxyl group in all solid forms, forming an acidMIDLINE HORIZONTAL ELLIPSISpyrimidine heterosynthon with COX inhibitor fenamic acids. To perform dissolution experiments and cell line analysis, the scale-up of both salt forms were done in the acetonitrile-methanol mixture through crystallization, which showed a polymorphic transformation in the case of PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named form II). The thermodynamic stability of PAZ+center dot FFA-center dot ACN (form II) and PAZ+center dot NFA- were analysed using slurry experiment under ambient conditions in pH 1.2 (0.1 N HCl) buffer medium and the residual solid phase was characterized by powder XRD, which showed that PAZ+center dot FFA-center dot ACN (form II) was a metastable solid form while PAZ+center dot NFA- was a stable solid form. The dissolution experiments at gastric pH 1.2 showed that the rate of dissolution of PAZ+center dot FFA-center dot ACN was 10 times higher than PAZ+center dot NFA-. The cell migration assay suggested that PAZ+center dot FFA-center dot ACN inhibited similar to 25% and PAZ+center dot NFA- inhibited similar to 20% migration of HUVEC cells compared to PAZ alone. These investigations suggested that the drug-drug salts PAZ+center dot FFA- and PAZ+center dot NFA- would be potential combo drug candidates for clinical trials. Multi-drug crystalline salts of pazopanib with fenamic acids exhibit enhanced dissolution and 20% higher inhibition in the migration of HUVEC cells compared to the reference drug.